Seletividade de agrotóxicos registrados para a cultura do milho a adultos de Trichogramma pretiosum Riley,1878 ( Hymenoptera : trichogrammatidae ) em laboratório. - Stefanello Júnior, Getulio Jorge (2007)
The selectivity of 64 pesticides registered to the culture were assessed to Trichogramma pretiosum Riley , 1879...................